Perceptions of Early Adult Women Toward the Narrative #MarriageIsScary on the TikTok Account @bobahagia19 - Aliya Asri Febrilia; Hamida Syari Harahap (Asosiasi Penelitian dan Pengajar Ilmu Sosial Indonesia, 2024)
The institution of marriage in Indonesia has long been considered a social and moral milestone. However, in the digital era, shifting gender roles and the rise of social media have significantly transformed how young women perceive marriage. This study aims to explore the perceptions of early adult women (aged 18–25) toward the #MarriageIsScary narrative on TikTok, focusing on content from the account @bobahagia19. The research employs a qualitative descriptive approach using interviews, observations, and content analysis of selected TikTok videos. The findings reveal that the #MarriageIsScary trend represents a collective expression of emotional anxiety, self-awareness, and social critique of traditional marriage norms. Participants perceived marriage as an uncertain institution, often associated with emotional instability, betrayal, and loss of autonomy. Yet, the same discourse also fostered empowerment and solidarity among women, forming what scholars describe as digital sisterhood. The discussion integrates sociological and media theories (Giddens, 1992; Papacharissi, 2015; Banet-Weiser, 2018) to illustrate how digital narratives both reflect and reshape cultural meanings of marriage in contemporary Indonesia. Overall, the study concludes that TikTok functions as a participatory space where young women redefine marital expectations through shared emotions, storytelling, and online community engagement.